2013
DOI: 10.1159/000350556
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Coxsackievirus B4, Feline Calicivirus and Herpes Simplex Virus Type 1: Unexpected Virucidal Effect of a Disinfectant on a Non-Enveloped Virus Applied onto a Surface

Abstract: Objective: To evaluate the effect of a disinfectant onto viruses in suspension on the one hand and applied onto a surface on the other. Methods: A system combining flocked swabs to recover viruses dried onto stainless steel carriers and gel filtration to eliminate cytotoxic products has been developed to study the virucidal effect of a quaternary ammonium-based disinfectant towards herpes simplex virus type 1 (HSV-1), coxsackievirus B4 (CVB4) and feline calicivirus F9 (FCV). The recovery of FCV has been estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…CVB4E2-positive strand RNA was quantitated by two-step quantitative RT-PCR as described previously ( 15 ). Briefly, total RNA was extracted with the RNeasy minikit (Qiagen, Valencia, California).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CVB4E2-positive strand RNA was quantitated by two-step quantitative RT-PCR as described previously ( 15 ). Briefly, total RNA was extracted with the RNeasy minikit (Qiagen, Valencia, California).…”
Section: Methodsmentioning
confidence: 99%
“…Non-enveloped viruses, such as coxsackieviruses, rotavirus, or poliovirus, can survive for extended periods on surfaces ( 9 , 10 ), while enveloped viruses, including H1N1 and human coronaviruses, remain infectious on surfaces after several days ( 6 ). The persistence of dried viruses is affected by various environmental conditions and factors such as heat, moisture, pH, and the type of surface ( 12 , 15 ). Furthermore, the compositions of media may also influence the persistence of viruses.…”
mentioning
confidence: 99%
“…CVB4E2 positive strand RNA was quantitated by two-step quantitative RT-PCR as described previously ( 25 ). Briefly, total RNA was extracted with RNeasy minikit (Qiagen, Valencia, Calif.) and resuspended.…”
Section: Methodsmentioning
confidence: 99%
“…Data from these studies revealed a complete or relative lack of efficacy of quaternary ammonium against all of the viruses tested [76,78,79]. In another study FCV applied on a surface, but not in suspension, was effectively inactivated by a quaternary ammonium-based disinfectant, while CVB4, an enterovirus, was resistant [80]. Ethanol has shown minimal efficacy against human norovirus and FCV, but it is active against MNV, with a clear dose-dependent impact [76,[81][82][83].…”
Section: Inactivation Of Enteric Viruses On Fomites: Chemical Disinfementioning
confidence: 99%